Cara Pandang Etnik Sasak yang Tercermin dalam Nyanyian Rakyat “Kadal Nongaq" - Nining Nur Alaini (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
Language and literature, as well as myth, painting, music, belief, and behavior are all simbols that have meanings. The symbolic forms have close links with the epistemological concepts of knowledge system of Sasak. Thus, the relationship between symbolic forms (literature or language) with a system of knowledge allows us to be able to know the knowledge of a particular system of reality or the perception of the world through their literature. Sasak system of knowledge of reality or the perception of the world can be revealed by examining the Sasak ethnic literature. This research revealed the system of Sasak knowledge of reality or perspective on the world and dismantled the cultural symbols that form the world view of the Sasak folk songs “Kadal Nongak”. The signs examined were icons,indexes, and symbols in folk songs “Kadal Nongaq”.